Managements Attitude Towards Employee Working in the Retail Shop in Bangladesh (Global Journal of Management and Business Research, 2023)
This study aimed at identifying Management s attitude towards employees working in retail shops in Bangladesh by exploring some factors that specify attitude The Study used descriptive statistics design This study was based on a field survey which was conducted in different areas of Chattogram Bangladesh Cluster Random sampling technique was used to pick up the sample The questionnaire was presented to 160 respondents in person all of them responded hence analyzed and presented in frequency distribution tables with their corresponding percentages and some statistics analysis Other data were sourced from published academic journals articles and other relevant materials on the internet The results indicate that Management in Retail Shop seems to have mildly negative attitude towards their employees The Study summed up that Management should have more focus on employees financial and Non financial benefits as those indicate the attitude of them towards employees in retail shops in Bangladesh
Keywords: management; attitude; employee; retail shop